Scheduling Tips For Drip Irrigation of Vegetables: AE259/AE092, 10/2014 - Haman, Dorota Z. (EDIS, 2014)
Florida's sandy soils are well known for their inability to hold water. Very little water is stored in the root zone, and excessive water applications result in the loss of mobile nutrients such as nitrogen, due to deep percolation. These soil properties require precise irrigation scheduling to avoid unnecessary loss of water and nutrients while providing a sufficient amount of water for optimum plant growth and production. This document presents scheduling tips for drip irrigation of vegetables.